THE EFFECT OF LEADERSHIP, COMPETENCE AND JOB TRAINING ON EMPLOYEE PERFORMANCE OF PT MEGA INTI MAKMUR MEDIKA - Sukhbir Singh; Fajar Rezeki Ananda Lubis; Sukmawan Satria (Institute of Computer Science (IOCS), 2022)
This study aims to examine and analyze the effect of leadership, competence and training on employee performance at PT Mega Inti Makmur Medika. The phenomenon of decreasing employee performance from decreased sales volume, leadership that is less active in supervising the work of employees and often not being present in supervising the work of employees directly, employees who occupy positions in the company still have education that is not in accordance with the position, employees are not able to understand the training material provided properly, besides that the training schedule held does not have a fixed schedule so this makes it difficult for employees to have maximum training results which is the background of this research. Simple random sampling was used as a sampling method. The sample used is 107 people. The data analysis method used multiple linear regression. In partial data testing, the leadership variable has a positive and significant effect on employee performance at PT Mega Inti Makmur Medika, competence has a positive and significant effect on employee performance at PT Mega Inti Makmur Medika, training has a positive and significant effect on employee performance at PT Mega Inti Makmur Medika. In testing the data analysis simultaneously, the variables of leadership, competence and training showed a positive and significant influence on employee performance at PT Mega Inti Makmur Medika.